Impact of breaking the language barrier on school education — Evidence from West Bengal in India - Agarwal, Sandip K.; Dutta, Souvik; Naha, Maharnab (Economics of education review, 2025)
This study examines the impact of reducing language barriers on educational outcomes in the state of West Bengal, India. Specifically, we analyze the effects of a policy reform that introduced question papers in Hindi for all subjects in grades 11 and 12 higher secondary examinations, aimed at supporting students in schools with Hindi as the language of instruction. Using school-level administrative data, we employ a difference-in-differences estimation strategy to identify the causal effects of the intervention on grade repetition and grade enrollment. Our findings reveal that the policy led to a decline in the share of repeaters and an increase in enrollment. This finding bears significant policy implications, particularly in educational settings where there is a mismatch between the language of instruction and the language used for assessment.